Cookies vs ciasteczka, engine vs silnik: the coexistence of English lexical and semantic loans in the Polish language of computer science - Zabawa, Marcin (Studia Anglica Posnaniensia, 2025)
Polish is under the continuous influence of English these days. In the past, this influence was generally restricted to overt borrowings, i.e., lexical loans, such as P. komputer ‘computer’ < E. computer. Nowadays, other types of loans are also evident, viz. covert borrowings, e.g., semantic loans, such as P. mysz ‘mouse’ used in the sense of ‘a device attached to a computer’. The usual scenario is that a given concept taken from English is rendered either by a lexical or semantic loan. In some cases, however, both lexical and semantic loans are used with identical meanings, e.g., P. cookies ‘small files’ < E. cookies coexisting with P. ciasteczka ‘cookies’ and P. engine ‘part of a programming code upon which a program, game, etc., is based’ < E. engine coexisting with P. silnik ‘engine’. The study is based on a corpus devised and compiled by the present author. The corpus consists of short informal texts (entries) taken from 32 selected Internet forums. The study shows that the coexistence of lexical and semantic loans (used with the same meanings) is not in doubt, but the phenomenon itself is not very frequent, viz. 29 such pairs have been identified. The coexistence is rarely equal, i.e., one term is usually clearly preferred and used more frequently than the other. This paper aims to analyse this type of “lexical loan – semantic loan” doublets and to specify the linguistic criteria that may be responsible for the preference for a lexical or semantic loan. The list of possible criteria discussed in the paper includes the criterion of length, morphological adaptation and potential for new derivatives, adaptation at the level of spelling, semantic transparency, frequency of exposure, international character, and time aspect.